2020
DOI: 10.3390/ijerph17165951
|View full text |Cite
|
Sign up to set email alerts
|

Social Economic Costs, Health-Related Quality of Life and Disability in Patients with Cri Du Chat Syndrome

Abstract: Background: Cri du Chat syndrome (CdC) is a rare disease caused by the deletion on the short arm of the chromosome 5, with an incidence of 1:15,000 to 1:50,000 live-born infants. No study at international level has assessed the costs, Quality of Life (QoL) and Disability through standardized quantitative tools. The aim is to estimate economic costs related to CdC from a societal perspective, to assess the QoL and Disability in patients with CdC along with their caregivers in Italy. Methods: A cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…In addition, HRQoL, perceived overall health, and subjective well-being are all important goals in mental health. Recently, cost-effectiveness has been emphasized when considering interventions for HRQoL [12][13][14][15][36][37][38]. Regarding the mental health care system, care managers may play important roles in improving HRQoL and reducing the cost of illness because they are considered to be key health care collaborators in the primary health care system [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HRQoL, perceived overall health, and subjective well-being are all important goals in mental health. Recently, cost-effectiveness has been emphasized when considering interventions for HRQoL [12][13][14][15][36][37][38]. Regarding the mental health care system, care managers may play important roles in improving HRQoL and reducing the cost of illness because they are considered to be key health care collaborators in the primary health care system [39].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, HRQoL is considered difficult to improve through medical intervention [11]. Previous studies reported some factors that affect HRQoL [12][13][14][15], and recent studies have emphasized the associations of depressive symptoms and cognitive complaints with HRQoL not only in individuals with mental illness but also in healthy individuals [7,8,16,17]. However, to our knowledge, how depressive symptoms and cognitive complaints are associated with HRQoL in Japanese adults remains relatively unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The data were analyzed and interpreted using conventional content analysis techniques, while the outline of the ecosystemic approach was derived from the focus group discussions and literature review [ 1 , 2 , 6 , 7 , 8 , 9 , 10 , 11 , 14 , 15 , 16 , 17 ]. The content analysis involves the coding of the key claims associated with distinct constructs highlighted by the focus group participants [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 80% of cases, they are of a genetic origin; in 70% of cases they affect children; and they are often incurable, advancing and life-threatening [ 1 ]. It is discernible that the wide-ranging difficulties confronted by healthcare systems in handling RDs extend to several factors, which pose major challenges for national governments [ 7 ]. The integration of these factors in a new intelligible and efficient structure necessitates innovative changes to the current setting in the field of RDs.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with RDs typically face late diagnosis, long-lasting and expensive treatment (if medication is even available), and social consequences [ 10 ]. For individuals affected by these largely unpreventable diseases, a comprehensive public health care approach, including the establishment of an operative RD ecosystem, would entail an important opportunity for more coherent and effective medical treatment [ 5 ].…”
Section: Identifying Salient Opportunities and Outlining Policy Recommendationsmentioning
confidence: 99%